2017
DOI: 10.5114/biolsport.2017.65999
|View full text |Cite
|
Sign up to set email alerts
|

Using lactate threshold to predict 5-km treadmill running performance in veteran athletes

Abstract: Measuring lactate threshold to predict endurance performance is difficult among veteran athletes, due to age-related decreases in net lactate concentration. The objective of this study was to determine whether lactate threshold, as assessed using the maximal deviation method (Dmax), which is not dependent on net values of lactate, could be used as a more valid measure of 5-km treadmill running performance than other methods of determining lactate threshold. Veteran runners (18 male and 18 female, aged 47.3±6.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
1
2
0
1
Order By: Relevance
“…It is worth mentioning that the RLT in our study showed limits of agreement (± 0.21 m·s -1 ) ( Fig. 3A ) that are only the half of the D max reported in the study of Forsyth et al [ 20 ] and thus illustrates its relevance as a predictor of endurance performance. Additionally, the fact that the RLT showed a very high correlation with MLSS and v5000m respectively indirectly confirms the MLSS as an important indicator of endurance performance.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It is worth mentioning that the RLT in our study showed limits of agreement (± 0.21 m·s -1 ) ( Fig. 3A ) that are only the half of the D max reported in the study of Forsyth et al [ 20 ] and thus illustrates its relevance as a predictor of endurance performance. Additionally, the fact that the RLT showed a very high correlation with MLSS and v5000m respectively indirectly confirms the MLSS as an important indicator of endurance performance.…”
Section: Discussionsupporting
confidence: 70%
“…The relationship between running performance and the anaerobic threshold has already been proven in previous studies [ 1 ], although concordance analyses have very rarely been reported so far. Besides correlation coefficients of 0.92 and 0.88 for D max and OBLA, Forsyth et al [ 20 ] also investigated the limits of agreement in relation to v5000m. D max showed the narrowest limits with ± 0.42 m·s -1 and OBLA the highest variability with ± 1.61 m·s -1 , which we confirmed in our study ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A análise do LAN pelo protocolo D-máx mostrou que este método foi superior ao Bi-segmentado, pelos resultados de alta confiabilidade (CCI = ,95) e forte correlação (r = ,91) entre as medidas. Apesar de haver uma lacuna sobre a aplicação deste critério em idosos, estudos têm validado o modelo por correlacioná-lo fortemente a MLSS 17,18 , ou por predições de desempenhos em provas de corrida 19 .…”
Section: Discussionunclassified
“…Previously, the velocity associated with the lactate threshold, CoT, and fat-free mass explained 71% of the variance in 5-km running performance in young runners [9]. In another study, the lactate threshold explained 84% of the variance in performance in a 5-km timed trial in veteran runners [10]. Therefore, metabolic and muscular strength parameters seem to be the main predictors of 5-km level-ground running performance.…”
Section: Introductionmentioning
confidence: 87%